Risks, Benefits, and the Optimal Time to Resume Deep Vein Thrombosis Prophylaxis in Patients with Intracranial Hemorrhage - Farr, Saman (Cureus, 2019)
Introduction It is common to start all patients on chemical prophylaxis for deep vein thrombosis (DVT) in order to decrease the risk of venous thromboembolism (VTE) and the associated adverse effects, including the potential for fatal pulmonary embolism (PE). There is no consensus in the literature on the optimal time to resume chemical DVT prophylaxis in patients who present with intracranial hemorrhage requiring neurosurgical intervention. The practice is variable and practitioner dependent. There can be difficulty in balancing the increased risk of further intracranial hemorrhage versus the benefit of starting DVT prophylaxis to prevent VTE. Method A retrospective review of patients that had diagnosis of intracranial hemorrhage (ICH) defined as epidural hematoma (EDH), subdural hematoma (SDH), or intra-parenchymal hematoma (IPH), was performed using the neurosurgical census at our institution. The review consisted of adult patients greater than 18 years old with a diagnosis of intracranial hemorrhage. Type of intracranial hemorrhage, method of neurosurgical intervention (whether surgical, bedside procedure, or both), day post-procedure prophylaxis was resumed, and the type of chemical prophylaxis used (subcutaneous heparin (SQH) versus enoxaparin) were recorded. The patient’s sex, Glasgow Coma Scale on presentation and discharge, length of hospital stay, and length of intensive care unit (ICU) stay were also recorded. Patients with previously diagnosed bleeding dyscrasia, previously diagnosed DVT or PE, patients without post-procedure cranial imaging (CT or MRI), and patients without post-procedure duplex ultrasound for DVT screening were excluded. Patients were monitored with head CT for possible expansion of ICH after resumption of therapy. Furthermore, we investigated whether the patient developed an adverse effect such as venous thromboembolism including deep vein thrombosis and/or pulmonary embolism during the post-procedure period when they were not on chemical prophylaxis. Results A total of 94 patients were analyzed in our study. Nine (9.6%) had an EDH, seventeen (18.1%) had an IPH, and sixty-eight (72.3%) had a SDH. The three most common procedures were craniectomy (28.7%), craniotomy (34%), and subdural drain placement (28.7%). The most common agent for chemical DVT prophylaxis was SQH in 78% of patients. There was no statistically significant association between type of chemical DVT prophylaxis used with respect to either ICU length of stay or hospital length of stay. Change in GCS (the difference of GCS on presentation versus on discharge) was found to have statistically significant relationship with the use of chemical DVT prophylaxis. Furthermore, patients were found to have no statistically significant association with re-bleed or new hemorrhage upon starting chemical DVT prophylaxis, regardless of the type of ICH. Conclusion The rates of DVT diagnosis did not seem to be significantly affected by the specific type of chemical prophylaxis that was used. ICU and hospital length of stay were not adversely affected by starting prophylaxis for VTE in patients with ICH. On the contrary, an improvement in GCS (on presentation versus discharge) was associated with starting chemical DVT prophylaxis in ICH patients within 24 hours post-procedure.